Realistic Reintegration After Imprisonment. A Sequence Analysis of the Labour Market Paths of Recently Incarcerated Individuals - Ramakers, Anke (The British journal of criminology, 2025)
Instead of focusing on the transition to work as an indicator of social integration after imprisonment, this study approaches reintegration as a process. The labour market paths of Dutch men were mapped using the number and type of transitions, their duration and order in the first four post-prison years. To identify seven clusters with diverse labour market paths, a distinction was made between various active labour market statuses (in school, employed) and passive labour market statuses (regular benefits, disability benefits, no formal income, detained). Characteristic of most clusters is that individuals experienced few transitions during the follow-up and spent little time in employment or in prison. These findings raise the question whether popular definitions of successful reintegration after imprisonment are realistic and point towards alternative definitions.